Roles of METTL3 and NLRP3 in pyroptosis and prospects in SCIRI - Guan, Xiaoqing; Zhang, Fengyi; Zhang, Ning; Li, Guangchun; Yin, Fei (Frontiers in immunology, 2025)
Spinal cord ischemia-reperfusion injury (SCIRI) leads to severe neurological deficits, with pyroptosis emerging as a key driver of inflammation and neuronal death. Recent studies suggest that methyltransferase-like 3 (METTL3), a critical RNA methyltransferase, may regulate the nucleotide-binding oligomerized structural domain-like receptor protein 3 (NLRP3) inflammasome activation via N6-Methyladenosine (m6A) modification, yet direct evidence in SCIRI remains limited. This review synthesizes current knowledge on the METTL3-NLRP3 axis in pyroptosis, explores its therapeutic potential, and identifies critical research gaps for future investigation.